Pandemic influenza preparedness: Africa at the crossroads - Oluyemisi C. Ijamakinwa; Niamh Stephenson (AOSIS, 2012)
At least two distinct approaches to pandemic preparedness have arisen in response to the threats posed by pandemic influenza: a traditional public health approach and an increasingly securitised one. Traditional public health focuses on the population and their living conditions. In contrast, public health strategies informed by concerns with security focus on the resilience of critical infrastructure, such as electricity and communication, and on the ensuring good connections between different layers of government and any private bodies likely to be central to the response. Pandemic plans can be informed by one or a mix of both approaches. The securitised approach is more prevalent in the World Health Organization (WHO)'s plans and Western countries' plans. In contrast, the WHO-AFRO Regional Pandemic Influenza Preparedness Plan 2009 utilises the existing Integrated Diseases Surveillance and Response framework as its starting point. It is informed by both rationales. Will African preparedness efforts develop in the direction of those already more informed by concerns about security? This paper examines how a securitised approach glosses over the differences between existing and threatened diseases. This is a particular problem in the African context with a high burden of infectious disease and underfunded health systems. Rather than a diversion of resources into a securitised approach, we suggest that the preparedness needs of the African continent are best served by focussing political will, international aid, financial and technical resources on the development of the health sector, including the integrated diseases surveillance and response framework. By tracing the distinct rationales at work in preparedness plans, it becomes apparent that an emphasis on the population will better position the continent for the future pandemics.